2012
DOI: 10.3389/fpsyt.2012.00081
|View full text |Cite
|
Sign up to set email alerts
|

Parietal Contributions to Visual Working Memory Depend on Task Difficulty

Abstract: The nature of parietal contributions to working memory (WM) remain poorly understood but of considerable interest. We previously reported that posterior parietal damage selectively impaired WM probed by recognition (Berryhill and Olson, 2008a). Recent studies provided support using a neuromodulatory technique, transcranial direct current stimulation (tDCS) applied to the right parietal cortex (P4). These studies confirmed parietal involvement in WM because parietal tDCS altered WM performance: anodal current t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
92
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(106 citation statements)
references
References 117 publications
(146 reference statements)
10
92
4
Order By: Relevance
“…Considering the complexity of the model of three independent attention networks the ANT comprises, a separation of, e.g., low vs. high performing individuals based upon the ANT data is not as straight forward as in the study by Jones and Berryhill (2012) mentioned above and our subject number was too small for a valid multifactorial analysis.…”
Section: Tdcs Stimulation-effects Of Inter-individual Differencesmentioning
confidence: 98%
See 1 more Smart Citation
“…Considering the complexity of the model of three independent attention networks the ANT comprises, a separation of, e.g., low vs. high performing individuals based upon the ANT data is not as straight forward as in the study by Jones and Berryhill (2012) mentioned above and our subject number was too small for a valid multifactorial analysis.…”
Section: Tdcs Stimulation-effects Of Inter-individual Differencesmentioning
confidence: 98%
“…In participants with high working memory (WM) capacity, Jones and Berryhill (2012) uncovered selective effects of rPPC tDCS (anodal or cathodal) when WM task difficulty was increased: In the high WM capacity group, the effect of PPC tDCS (anodal or cathodal) followed a linear function as WM task difficulty increased with set size, while in the low WM capacity group, PPC tDCS (anodal or cathodal) impaired WM performance (Exp 1) or left it unchanged (Exp 2). The authors speculated that low WM capacity individuals may not recruit the PPC for WM tasks as efficiently as high WM capacity individuals.…”
Section: Tdcs Stimulation-effects Of Inter-individual Differencesmentioning
confidence: 99%
“…Anodal stimulation over the right inferior frontal cortex has consistently shown to speed up object detection. Perhaps this success can be attributed to the challenging nature of the task: tES effects might be greatest for difficult tasks with plenty of room for improvement (e.g., Jones and Berryhill 2012). Because this task is more complex than the typical visual search paradigm, it could also be that tDCS affected other processes such as threat detection or scene perception, and not those underlying visual search per se.…”
Section: Visual Searchmentioning
confidence: 99%
“…However, recent studies also report a drop in performance following anodal tDCS (Ferrucci et al, 2008;Jones and Berryhill, 2012;Kaminski et al, 2013;Zwissler et al, 2014;Schaal et al, 2015) or improvements following cathodal tDCS (Smirni et al, 2015). A recent tDCS study reported a significant decrease in performance in an old/new recognition task following anodal tDCS over the left PFC during encoding of pictures (Zwissler et al, 2014).…”
Section: Verbalmentioning
confidence: 97%